2015
DOI: 10.1007/s00441-015-2287-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex and the preimplantation embryo: implications of sexual dimorphism in the preimplantation period for maternal programming of embryonic development

Abstract: The developmental program of the embryo displays a plasticity that can result in long-acting effects that extend into post-natal life. In mammals, adult phenotype can be altered by changes in the maternal environment during the preimplantation period. One characteristic of developmental programming during this time is that the change in adult phenotype is often different for female offspring than for male offspring. In this paper, we propose the hypothesis that sexual dimorphism in preimplantation programming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 83 publications
(167 reference statements)
0
43
2
Order By: Relevance
“…[72] In fact, many diseases with early developmental origins display sex biases. In the same vein, the sex of the embryo can be considered an additional "environmental" or programming factor in the establishment of the epigenome.…”
Section: Embryos Exhibit Sex-specific Responses To the Maternal Envirmentioning
confidence: 99%
See 2 more Smart Citations
“…[72] In fact, many diseases with early developmental origins display sex biases. In the same vein, the sex of the embryo can be considered an additional "environmental" or programming factor in the establishment of the epigenome.…”
Section: Embryos Exhibit Sex-specific Responses To the Maternal Envirmentioning
confidence: 99%
“…In the same vein, the sex of the embryo can be considered an additional "environmental" or programming factor in the establishment of the epigenome. [41,72] Also, there are evocative reports of sex-specific signaling by the embryo to the mother. [73,74] Studies in rodent, bovine, and human blastocysts have shown that the response to environmental conditions is different in male and female embryos, [75,76] reflecting differences in their metabolism.…”
Section: Embryos Exhibit Sex-specific Responses To the Maternal Envirmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, glucose does not always inhibit preimplantation development, indicating that the response is variable . Furthermore, there is not only sexually dimorphic gene expression preimplantation but also considerable variation in that gene expression between individual embryos, and the sex‐specific responses are influenced by maternal regulatory factors that vary with the maternal environment . Together, these studies suggest that there is variation in responsiveness and potential for maternal control, suggesting avenues for future research.…”
Section: Evolutionary Significance: Do Mechanisms Indicate Facultativmentioning
confidence: 98%
“…Similarly, livestock embryos conceived by artificial insemination (AI) or produced in vitro and transferred to recipients are prone to early embryonic death resulting in early pregnancy losses that lower AI conception rates down to 35-45 % and account for millions of lost dollars in the beef and dairy cattle industries (Hansen et al 2004). In this regard, P. Hansen et al discuss the sex-specific expression of colony stimulating factor CSF2 (Loureiro et al 2009) and related mechanisms guiding preimplantation embryo programming, which leads to the establishment and sustenance of pregnancy, a developmental milestone that is equally important for the management of human and animal reproductive health (Hansen et al 2015). Among possible causes of preimplantation embryo changes that may lead to developmental arrest and epigenetic abnormalities, the endoplasmatic reticulum stress (Hao et al 2009), caused by exogenous factors during laboratory procedures necessary for human/animal embryo production, is discussed by Latham (2015).…”
Section: Introductionmentioning
confidence: 99%